Applicability of the Filter Paper Technique for Detection of AntifilarialIgG4 Antibodies Using the Bm14 Filariasis CELISA - Hayley M. Joseph; Wayne Melrose (Journal of Parasitology Research)
Demonstration of successful elimination of lymphatic filariasis (LF) in endemic countries requires sensitive diagnostics for accurate definitions of endpoints and future surveillance. There has been interest in complementing available diagnostics with antibody serology testing in children, since negative serology would correspond with cessation of LF transmission. The Filariasis CELISA detects antifilarial IgG4 and has favourable results with serum samples but field application requires an easier sampling method. Ninety-four paired plasma and filter paper samples were assayed with promising results. The filter paper method resulted in a sensitivity of 92% and a specificity of 77% when compared to the paired plasma. One hundred and one filter paper samples were assessed for storage effects. Following 10-month storage at −20∘C there was a significant reduction in reactivity (𝑃<.001). Overall the results indicated that filter paper sampling would be a favourable sensitive and specific alternative for blood collection in surveys.